Gaya Bahasa Sindiran pada Acara Talk Show Tonight Show di NET TV - Azirah, Siti; Idawati, Idawati; Aziz, Abdul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to describe the form, function, and meaning of satire language style in the Talk Show Tonight Show on NET TV. This study uses a qualitative method with a descriptive research design. The data sources in this study come from several episodes on the YouTube social media account TonightShowNet. The data analysis used is a stylistic approach that is carried out in detail starting from data identification, data classification, analyzing and interpreting data, and data presentation. The research data were obtained by grouping satire language style in the form of words, phrases, and sentences contained in the Talk Show Tonight Show. The results of the study show that in several episodes of Tonight Show, five forms of satire language style were found, namely irony, cynicism, sarcasm, satire, and inuendo. The functions of satire language style found include social criticism, entertainment, and building closeness. This study also identified two types of meaning contained in satire language style, namely connotative meaning and denotative meaning. Thus, the satirical style of language in